Gender Normativity in the Educational Environment: A Case Study with Transgender Students - España-Chico, Celia (2023)
Introduction. Historically, alternative sexualities have endured social and institutional violence. Despite this, research analyzing personal experiences within educational environments remains scarce. Objective. The objective of this research was to explore the various manifestations of sexual normativity in schools and its effects on transgender students. Method. The semi-structured interview technique was employed, validated by a panel of experts. Two participants were involved: the grandmother of a six-year-old transgender girl and her teacher. Results. Sexual normativity manifested at three levels: institutional (macrosystem), school (mesosystem), and personal (microsystem). Specific results include the need for specific policies and media influence at the first level, the ignorance and resistance of the school at the second level, and stereotypical practices, ad hoc violence and its impact at the third level. Conclusions. The absence of specific policies, the shortage of training in this regard and prejudices can hinder the free expression of sexual and gender diversity at school.